Nyūmon modan Linux on puremisu kara kuraudo made, habahiroi chishiki o etokusuru - Hausenblas, Michael (Orairī Japan, 2023)
"If you use Linux in development or operations and need a structured approach to help you dive deeper, this book is for you. Author Michael Hausenblas also provides tips and tricks for improving your workflow with this open source operating system. Whether you're a developer, software architect, or site reliability engineer, this hands-on guide focuses on ways to use Linux for your everyday needs, from development to office-related tasks." --
Keywords: Linux; Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems